Tropical peat subsidence, nutrient losses and oil palm seedling growth due to different water table depths - Abubakar, Safiyanu Hashim (2018)
Agricultural development on tropical peat land, which is characterized by highly acidic in nature, low nutrients status and high water table depths has been strongly criticized by the international community. Peat soils are unsuitable for cultivation in their natural states, but upon proper soil management and amendments, they can be converted for plantation crops such as oil palm, sago and pineapple with yield performances, at times, matching those on mineral soils. High water table and low nutrients availability are identified as the common problem in peat soils. Rapid changes of water table results in leaching losses of applied nutrients, making them unavailable for crops growth and development. As such, frequent monitoring of water table has become necessary. The objectives of this study were to determine the effects of several water table depths on the (1) Nutrient losses (N, P, K, Mg, Ca, Cu, and Zn), ammonia volatilization following application of urea, and tropical peat subsidence. (2) Oil palm seedlings vegetative growth using a high-density polyethylene containers. Fifteen cylindrical lysimeters were constructed from a high-density polyethylene (HDPE) material, measuring 0.50 m in diameter and 1 m in height. They were set up to mimic the natural conditions of drained peats. The experiment was carried out in a randomized completely block design. The experiment consisted of five different water table depths (25, 40, 55, 70, and 85 cm) from the soil surface with three replication each. The water tables in the experiment were controlled based on the oil palm root zone depths according to the water table management that was used in tropical peat soil grown with oil palm. The water table depth were adjusted after rainfall events based on the actual water table depths. Leachate samples were collected after every rainfall event and analysed for N, P, K, Mg, Ca, Cu, and Zn contents. A total of 46 days rainfall events were recorded during the study period. A closed dynamic air flow system method was used to measure the daily ammonia loss from urea applied. The amount of urea applied to the peat soil were scale down according to the volume of the lysimeter in the field and volume of the plastic container used where 2 g of urea was surface applied to each of the plastic container containing 1533.02 g peat soil. The system was made of exchange chamber of air pump with the flow rate ranges between 1 and 3.5 L min-1, exchange chamber of (2670 mL plastic container) and a trap (250 mL Erlenmeyer flask). Ammonia loss from the soil was collected using a boric acid by air flow circulation that was passed through the exchange chamber into a trapping flask containing 75 mL boric acid mixed with bromocresol green and methyl red indicator. Based on rainfall events high water table depths (25 cm) showed higher nutrient leaching losses where they accounted for 22.3 N, 27.3 P, 22.3 K, 26.6 Mg, 24.4 Ca, 28.3 Cu, and 27.2 % Zn. The presence of high amount of water may had a major role in leaching losses which made the peat soil always moist and rendered the nutrients more soluble such that their loss from the soil were rapid. Tropical peat subsidence was higher for lower water table depths, where the water table depths 25, 40, 55, 70 and 85 cm (from the soil surface) subsided by 1.9, 2.2, 4.2, 4.6 and 5.6%, respectively. The total plant biomass weight for different water table depths, 25, 40, 55, 70, and 85 cm were 118, 211, 792, 250 and 189 g, respectively. There was a significant difference among the treatment. Fifty-five cm gave the highest biomass growth. High ammonia loss was recorded from high water table (3 cm) accounting for 35.5 % of total ammonia loss with regards to low water table (15 cm) that account only 7.7 %. Water table depth significantly affects nutrients leaching loss, subsidence, oil palm growth and ammonia loss on tropical peat soil cultivated with oil palm.